2007
DOI: 10.1016/j.atherosclerosis.2006.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of carotid atherosclerotic plaque progression as measured by noninvasive magnetic resonance imaging

Abstract: The purpose of this in vivo MRI study was to quantify changes in atherosclerotic plaque morphology prospectively and to identify factors that may alter the rate of progression in plaque burden. Sixtyeight asymptomatic subjects with ≥50% stenosis, underwent serial carotid MRI examinations over an 18 month period. Clinical risk factors for atherosclerosis, and medications were documented prospectively. The wall and total vessel areas, matched across time-points, were measured from cross-sectional images. The nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
83
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 22 publications
13
83
1
1
Order By: Relevance
“…Table 3 provides an overview of prior studies 15, 29, 30. Many factors influence the overall changes in atherosclerosis including study population, prior statin therapy, and intensity of statin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 provides an overview of prior studies 15, 29, 30. Many factors influence the overall changes in atherosclerosis including study population, prior statin therapy, and intensity of statin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Tahara et al observed that the attenuation of plaque inflammation caused by statins can be monitored by 18 F-FDG PET/CT (10). Another study demonstrated that statin therapy is associated with reduced rates of plaque progression among individuals with asymptomatic carotid atherosclerosis (24). Because statins exhibit a variety of cholesterol-independent, plaque-stabilizing effects involved in endothelial function, cell proliferation, inflammatory response, and lipid oxidation, they might ultimately affect 18 F-sodium fluoride uptake (25).…”
Section: Comparison To Other Pet Tracers and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Statin treatment has been shown to induce reduced progression or even regression of plaque burden. [19][20][21][22][23][24][25] Approximately 90% of patients in our study were using statins during the follow-up period. Thirty-one percent of our patients showed plaque regression, a number similar to that found in other plaque progression studies in which most patients were on statin therapy.…”
Section: Discussionmentioning
confidence: 88%
“…In a prospective MR imaging study, Saam et al described a yearly increase of 2.2% in wall area in Ͼ50% stenosed carotid arteries. 19 Boussel et al found an annual rate of progression of carotid vessel wall volume of 2.3% per year in arteries with Ͼ50% stenosis. 20 In these studies, however, the included arteries had more severe stenosis compared with the arteries included in our study.…”
Section: Discussionmentioning
confidence: 99%